MEMAKNAI JIHAD DALAM AL-QUR'AN DAN TINJAUAN HISTORIS PENGGUNAAN ISTILAH JIHAD DALAM ISLAM - Fattah, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
A narrow understanding by some Muslims about jihad will bring a radical group that led to the appearance of movements that harm Muslims. To find out how the jihad in the Qur'an and how to phase in the use of the word jihad, it would require a comprehensive understanding by identifying the verses of the Qur'an and understanding of the historical decline in these verses. This article examines the identification of passages which there is a derivation the word jihad and then sorted according to time of down (Makkiyyah and Madaniyyah). The article concludes that the word jihad and derivation in the Qur'an is mentioned 41 times and separated at 19 surah. Not all of the word jihad and it derivation means war, but historically it is known that jihad also has other meanings and reduced in accordance with the conditions of the situation at that time.Â Keywords: jihad, al-Qur'an, historical